Synthesis of 3-acyltetramates by side chain manipulation and their antibacterial activity - Tan, S; Chai, C; Moloney, M (Royal Society of Chemistry, 2014)
An efficient approach for the introduction of 3-acyl side chain groups onto a core tetramate system, which are suitable for further manipulation by nucleophilic displacement or Horner-Wadsworth-Emmons coupling, provides access to a diverse library of substituted tetramates related to two distinct classes of natural products, equisetin and pramanicin. Assessment against S. aureus and E. coli indicated that some compounds exhibit significant antibacterial activity, providing unusual leads for further optimisation in the drug discovery process.